The Relationship Between Body Mass Index and Blood Sugar Levels In Students of The Faculty of Medicine, University of Muhammadiyah North Sumatera 2021 - Maghriba, Gilang; Damayanti, Amelia (Indonesian Journal Publisher, 2025)
Blood sugar levels are the glucose present in the blood originating from carbohydrates in meals and can be stored in the form of glycogen in the liver and skeletal muscles. If blood sugar levels are excessively high, it can lead to a condition called hyperglycemia, which if left untreated can lead to a metabolic disorder called Diabetes Mellitus. Diabetes mellitus has several complications, one of which is obesity. BMI is one of the methods used to determine whether a person is affected by diabetes or not. To investigate the relationship between body mass index (BMI) and fasting blood sugar levels among students of the 2021 intake at the Faculty of Medicine, University of Muhammadiyah North Sumatra. A cross-sectional approach was used, with data collected once at the same time. Data was collected using a glucometer to measure fasting blood sugar levels, an analog scale to measure body weight, and a stature meter to measure height. The Mann-Whitney test for body mass index with fasting blood sugar levels yielded a result of P>0.05. The result of this study is that there is no relationship between BMI and fasting blood sugar levels among students.